Clinical, psychosocial, and demographic factors associated with health-related quality of life profiles of women with breast cancer in early phases of survivorship - Graves, Kristi D.; Fall-Dickson, Jane M.; Reeve, Bryce B.; Lin, Li; Ahn, Jaeil; Pan, Wei; Potosky, Arnold L. (Journal of psychosocial oncology research and practice, 2025)
Supplemental Digital Content is Available in the Text. AbstractBackground:We aimed to identify health-related quality of life (HRQOL) profiles among breast cancer survivors and factors associated with each profile.Methods:Breast cancer survivors diagnosed 6-13 months earlier completed surveys assessing sociodemographic, clinical, and HRQOL variables (NIH PROMIS short forms). Using latent profile analysis (LPA), we grouped survivors into HRQOL profiles of PROMIS scores based on model fit and clinical interpretability. We used multinomial logistic regression models to determine clinical, psychosocial, and demographic factors associated with each HRQOL profile.Results:Among 1,638 breast cancer survivors, we identified four HRQOL profiles: high (20.3% of survivors), average (34.5%), low (33.1%), and very low (12.1%). Membership in the low or very low versus high HRQOL profile was associated with: <high school versus college/graduate [low OR = 2.98 (1.29, 6.85); very low OR = 4.51 (1.53, 13.33)]; not working [low OR = 2.20 (1.41, 3.43); very low OR = 4.32 (2.33, 8.00)]; lack of consistent companionship [low OR = 3.67 (1.85, 7.25); very low OR = 6.22 (2.78, 13.92)]; and history of: lung condition [low OR = 2.42 (1.34, 4.36); very low OR = 4.28 (2.09, 8.77)]; anxiety/depression [low OR = 2.76 (1.71, 4.46); very low OR = 8.86 (4.74, 16.56)]; sleep disturbance [low OR = 2.97 (1.25, 7.06); very low OR = 6.21 (2.40, 16.08)]; and chemotherapy [low OR = 3.29 (2.13, 5.08); very low OR = 7.34 (3.75, 14.37)]. Protective factors associated with reduced likelihood of low/very low HRQOL profile membership included higher: financial well-being [low OR = 0.82 (0.74, 0.90); very low OR = 0.78 (0.68, 0.89)] and spirituality [low OR = 0.63 (0.56, 0.71); very low OR = 0.53 (0.45, 0.62)].Conclusion:About 45% of early-phase breast cancer survivors in the present sample experienced low or very low HRQOL; early identification and targeted interventions can be used to improve HRQOL over time.